Validating Learning Organization in the Medical Profession: A Preliminary Analysis - Rana Zeeshan Mubarak; Marinah Awanag; Naveed R. Khan; Sadia Mubarak (International Journal of Experiential Learning & Case Studies, 2020)
This study investigates the underlying pattern of learning organisation practices among medical doctors using Learning Organization Survey (LOS) designed by Garvin, Edmondson and Gino (2008). The instrument was modif ied to adapt to settings in clinical care. A preliminary data of 150 medical doctors were used for reliability and exploratory factor analysis (EFA). Cronbach’s alpha indicated an excellent reliability score. The outcome of EFA was a seven-factor solution. While some subscales converged to new factors, the three building blocks of a learning organisation successfully retained the original items. The outcomes reveal that LOS in the context of medical vocation is reliable and valid at an initial stage. The three building blocks of a learning organisation as specif ied by Garvin et al. (2008) can, therefore, be instrumental in fostering continuous learning in medical vocation. The conception of the learning organisation, albeit important for continuous development of human resources for health in the 21st century, was not well researched in medical vocation. The present study, in this context, is an initial analysis that suggests grounds for future research. The findings call for further enquiries with an expanded sampling framework as well as further validation on LOS using conf irmatory factor analysis